Differential expression of slow and fast-repriming tetrodotoxin-sensitive sodium currents in dorsal root ganglion neurons - Tan, Zhi-Yong; Wu, Bin; Su, Xiaolin; Zhou, You; Ji, Yong-Hua (Frontiers in Molecular Neuroscience, 2024)
Sodium channel Nav1.7 triggers the generation of nociceptive action potentials and is important in sending pain signals under physiological and pathological conditions. However, studying endogenous Nav1.7 currents has been confounded by co-expression of multiple sodium channel isoforms in dorsal root ganglion (DRG) neurons. In the current study, slow-repriming (SR) and fast-repriming (FR) Tetrodotoxin-sensitive (TTX-S) currents were dissected out electrophysiologically in small DRG neurons of both rats and mice. Three subgroups of small DRG neurons were identified based on the expression pattern of SR and FR TTX-S currents.Majority of rat neurons only expressed SR TTX-S currents while majority of mouse neurons expressed additional FR TTX-S currents. ProTx-II inhibited SR TTX-S currents with variable efficacy among DRG neurons. Expression of both types of TTX-S currents was higher in Isolectin B4-negative (IB4 -) compared to Isolectin B4-positive (IB4 + ) neurons. Paclitaxel selectively increased SR TTX-S currents in IB4 -neurons. In simulation experiments, the Nav1.7expressing small DRG neuron displayed lower rheobase and higher frequency of action potentials upon threshold current injections compared to Nav1.6. The results suggested a successful dissection of endogenous Nav1.7 currents through electrophysiological manipulation that may provide a useful way to study the functional expression and pharmacology of endogenous Nav1.7 channels in DRG neurons.